The Role of Development in the Dynamic Relationship between Moral Agency and Peer Delinquency - Walters, Glenn D. (Journal of developmental and life-course criminology, 2023)
The purpose of this study was to determine whether a change in moral agency was capable of predicting a change in peer delinquency, whether a change in peer delinquency was capable of predicting a change in moral agency, and whether the effects were reciprocal. Based in part on prior research showing that the peer selection effect often precedes the peer influence effect developmentally, it was further hypothesized that a change in moral agency leading to a change in peer delinquency would be stronger than the alternate path during the early years of adolescence. These hypotheses were tested in a group of 1,830 middle school students who were followed from age 12 to age 16 and a group of 2,138 high school students who were followed from age 15 to age 17. Findings were generally supportive of the hypotheses: a change in moral agency led to a change in peer delinquency at all three ages, a change in peer delinquency led to a change in moral agency in mid-to-late adolescence, and peer selection (moral agency → peer delinquency) was significantly stronger than peer influence (peer delinquency → moral agency) in early adolescence but not in middle adolescence or mid-to-late adolescence. These findings suggest that the relationship between moral agency and peer delinquency is dynamic, reciprocal, at least during the latter stages of adolescence, and sequential.